Analiza elegii Budae a Turcis occupatae querela ze zbioru Tristiów Klemensa Janickiego - Zaborowska-Musiał, Justyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Analiza elegii Budae a Turcis occupatae querela ze zbioru Tristiów Klemensa Janickiego (The analysis of the elegy Budae a Turcis occupatae querela of Klemens Janicki’s Tristia). This article contains the analysis of the so far little researched elegy from the book of Tristia by an Early Modern Polish poet Klemens Janicki (Clemens Ianicius) written after the Turks conquered Buda in the summer of 1541. The analysis focuses on the composition of Janicki’s elegy, the method and means used by the poet to get the recipients to take action against Turkey imperiling Europe.